When the PCAOB Talks, Who Listens? Evidence from Client Firm Reaction to Adverse, GAAP-Deficient PCAOB Inspection Reports - Abbott, Lawrence J. (Institutional Knowledge at Singapore Management University, 2008)
In an effort to increase the transparency and quality of the public auditing profession, the Sarbanes-Oxley Act created the Public Company Accounting Oversight Board (PCAOB). Under the Sarbanes-Oxley Act, the PCAOB was granted inspection rights to 'audit' auditors and their respective audit processes. The PCAOB is an independent, private sector body that has replaced the American Institute of Certified Public Accountants peer review system. The results of PCAOB inspections are summarized in publicly-available reports that are readily accessible at the PCAOB's website. We posit that due to the objectivity, specificity, variation and visibility of these reports, the PCAOB has created a powerful public signal of perceived audit quality. We hypothesize that registrants with high potential agency conflicts have incentive to switch away from auditors that have received an adverse, GAAP-deficient PCAOB report. In addition, we argue that effective audit committees have similar motivation to switch away from such auditors. Using logistic regressions, we document a strong agency-based demand for perceived audit quality as proxied by the PCAOB inspection reports. We also show that effective audit committees are particularly sensitive to the receipt of a GAAP-deficient PCAOB inspection report and are much more likely to switch auditors subsequent to the inspection report disclosure. Our evidence on the cross sectional differences of clients' reactions to PCAOB inspection reports contribute to the understanding of auditor industry regulations.